Length-weight relationships and condition index of Pokea clams (Batissa violacea var. celebensis, von Martens 1897) in the Laeya River, Southeast Sulawesi, Indonesia - Bahtiar, Bahtiar; Findra, Muhammad Nur; Ishak, Ermayanti (Aceh Journal of Animal Science, 2023)
The length-weight relationship and condition index of pokea clams in the Laeya River are not fully known. This study was aimed to determine the length-weight relationship and condition index of pokea clams in the Laeya River, Southeast Sulawesi. This research was conducted 10 months from May 2016 to February 2017 in the Laeya River, Southeast Sulawesi. Pokea clams are collected using a shovel. The length and weight of each clam was using calipers and analytical scales with accuracy of 0.05 mm and 0.01 g, respectively. The weight of the shell and dried meat was obtained by drying the shells first using an oven and weighing using an analytical balance with an accuracy of 0.01 g and 0.0001 g, respectively. The results showed that the relationship between length and weight of pokea clams in males and females were 2.61 and 2.78, respectively; with R2values of 0.89 and 0.93, respectively. The highest b values for males and females were found in July with values of 3.03 and 2.94, respectively. The lowest b value was found in November with values of 2.45 and 2.46, respectively. The condition index values for males and females were 4.7 2.2 and 5.17 2.32, respectively. The highest condition index was found in May with values of 6.00 3.07 and 7.83 2.55, respectively. The condition index values for males and females increased with increasing shell size. Male and female at the largest size (6.01-6.05 cm) had the highest index with values of 8.05 6.41 and 9.12 3.38, respectively. In conclusions, the growth was negative allometric pattern, condition index was in fat category, and had peak spawning in July and experienced partial spawning in September-February.